The Combined Use of Orf Virus and PAK4 Inhibitor Exerts Anti-tumor Effect in Breast Cancer - Deng, Hao; Xiao, Bin; Huang, Yinger; Weng, Kongyan; Chen, Jialing; Li, Kun; Wu, Hongfeng; Luo, Shuhong; Hao, Wenbo (Frontiers in Microbiology, 2022)
The parapoxvirus Orf virus (ORFV) has long been recognized as one of the valuable vectors in researches of oncolytic virus. In order to develop a potential therapeutic strategy for breast cancer based on the oncolytic virotherapy via ORFV, firstly we explore the oncolytic effects of ORFV. Our research showed that ORFV exerts anti-tumor effects in vitro by inducing breast cancer cell G2/M phase arrest and cell apoptosis. In vivo experiments were carried out, in which we treated 4T1 tumor-bearing BALB/C mice via intratumoral injection of ORFV. ORFV can exert anti-tumor activity by regulating tumor microenvironment and inducing a host immune response plus directly oncolytic effect. The CRISPR-Cas9 knockout library targeting 507 kinases was used to screen out PAK4, which is beneficial to the anti-tumor effect of ORFV on breast cancer cells. PF-3758309 is a potent PAK4-targeted inhibitor. Co-using of ORFV and PF-3758309 as a combination treatment produces its anti-tumor effects through inhibition of cell viability, induction of apoptosis and suppression of cell migration and invasion in vitro. The results of in vivo experiments showed that the tumor growth of mice in the combination treatment group was significantly inhibited, which proved that the combination treatment exerts an effective anti-tumor effect in vivo. In summary, we have clarified the oncolytic effect of ORFV on breast cancer, and found that the combination of ORFV and PAK4 inhibitor can effectively improve the oncolytic effect of ORFV. We hope our research could provide a new idea for the development of new treatment strategies for breast cancer.